Secretion and Function of Pituitary Prolactin in Evolutionary Perspective - Dobolyi, Arpád; Oláh, Szilvia; Keller, Dávid; Kumari, Rashmi; Fazekas, Emese A.; Csikós, Vivien; Renner, Éva; Cservenák, Melinda (Frontiers in Neuroscience, 2020)
The hypothalamo-pituitary system developed in early vertebrates. Prolactin is an ancient vertebrate hormone released from the pituitary that exerts particularly diverse functions. The purpose of the review is to take a comparative approach in the description of prolactin, its secretion from pituitary lactotrophs, and hormonal functions. Since the reproductive and osmoregulatory roles of prolactin are best established in a variety of species, these functions are the primary subjects of discussion. Different types of prolactin and prolactin receptors developed during vertebrate evolution, which will be described in this review. The signal transduction of prolactin receptors is well conserved among vertebrates enabling us to describe the whole subphylum. Then, the review focuses on the regulation of prolactin release in mammals as we have the most knowledge on this class of vertebrates. Prolactin secretion in response to different reproductive stimuli, such as estrogen-induced release, mating, pregnancy and suckling is detailed. Reproduction in birds is different from that in mammals in several aspects. Prolactin is released during incubation in avian species whose regulation and functional significance are discussed. Little information is available on prolactin in reptiles and amphibians; therefore, they are mentioned only in specific cases to explain certain evolutionary aspects. In turn, the osmoregulatory function of prolactin is well established in fish. The different types of pituitary prolactin in fish play particularly important roles in the adaptation of eutherian species to fresh water environments. To achieve this function, prolactin is released from lactotrophs in hyposmolarity, as they are directly osmosensitive in fish. In turn, the released prolactin acts on branchial epithelia, especially ionocytes of the gill to retain salt and excrete water. This review will highlight the points where comparative data give new ideas or suggest new approaches for investigation in other taxa.